Pengaruh Metode Cirkuit Training Terhadap Kecepatan Pemanjatan Wallclimbing Atlet Federasi Panjat Tebing Indonesia (FPTI) Dalam Jalur Speed Word Record - Arry Saputra; Raffly Henjilito (INSPIREE: Indonesian Sport Innovation Review, 2022)
The  purpose  of  the study. The goal of the study is to see how the circuit training approach affects the speed of wall-climbing by athletes from the Indonesian Rock Climbing Federation (FPTI) on the Pekanbaru City Speed World Record Line. Materials and methods. A research technique using an experimental methodology of one group pretest-post test design, in which a pretest is administered before therapy is administered. The study's population included the whole Indonesian Rock Climbing Federation (FPTI) Pekanbaru City, which included six male athletes. Results. We apply the t-test procedure to test the hypothesis, and we receive tcount = 7.01 from the t-value calculation, which we then compare to the ttable value. The value of ttable = 2.132 is known from table t, indicating that tcount is larger than ttable. As a result, the accepted hypothesis and the effect of circuit training on the ability to climb wall-climbing speed with a 19.31% increase in ability. Conclusions. Circuit training provides a 19.31% increase in speed for wall climbing athletes, according to data analysis